2018
DOI: 10.1002/jpln.201700093
|View full text |Cite
|
Sign up to set email alerts
|

What root traits determine grass resistance to phosphorus deficiency in production grassland?

Abstract: Grasslands are a major form of agricultural land use worldwide. Current and future declines of phosphorus (P) inputs into production grasslands necessitate a shift towards selecting grass species based on high efficiency under suboptimal, rather than optimal P conditions. It is therefore imperative to identify key root traits that determine P acquisition of grasses in soils with a low P status. In a 9‐month greenhouse experiment, we grew eight common grass species and cultivars on a soil with a low P status an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 50 publications
(64 reference statements)
4
31
0
Order By: Relevance
“…lower values for S b than in the current model) the maximum net C gain indeed corresponds to higher root length density. Although root length density is a more direct proxy of root surface area and therefore a main driver of nutrient uptake (Ros, de Deyn, Koopmans, Oenema, & van Groenigen, 2018;Ryser & Lambers, 1995), we found that the optimal C gain is achieved by a fourfold lower root length density in the second compared to the first scenario. For our model tree, this relatively low root length density may reduce resource uptake and hence C gain in the crown, but due to the low turnover rates of its fine roots, it can still achieve the highest C balance.…”
Section: Trees Can Increase Their C Balance Through Different Belowmentioning
confidence: 58%
“…lower values for S b than in the current model) the maximum net C gain indeed corresponds to higher root length density. Although root length density is a more direct proxy of root surface area and therefore a main driver of nutrient uptake (Ros, de Deyn, Koopmans, Oenema, & van Groenigen, 2018;Ryser & Lambers, 1995), we found that the optimal C gain is achieved by a fourfold lower root length density in the second compared to the first scenario. For our model tree, this relatively low root length density may reduce resource uptake and hence C gain in the crown, but due to the low turnover rates of its fine roots, it can still achieve the highest C balance.…”
Section: Trees Can Increase Their C Balance Through Different Belowmentioning
confidence: 58%
“…These were present across all of the FSC conditions on C3, on C2 in optimum N and low P, and on C5 in optimum N and P. One reason that these findings are of generic interest is that reports which provide resolution at the levels of specific markers or QTL in perennial ryegrass relating to root growth are rare due to the obvious experimental challenges in obtaining the necessary measurements. While there are a number of reports of QTL identification for different aspects of root growth from the cereals which, across different studies, have assigned QTL to all 7 of the Triticeae homoeologous chromosome groups [ 50 54 ], with similar findings in rice [ 52 , 55 62 ], most of the studies that have looked at root growth in perennial ryegrass have been population-based studies of root biomass [ 63 67 ]. Importantly, our findings establish that, as in cereals and rice, there is potential for selecting for root growth traits in perennial ryegrass if the right assays and populations are in place.…”
Section: Discussionmentioning
confidence: 99%
“…Whole root system, absorptive roots Lynch et al, 2011;Laliberté et al, 2015;Ros et al, 2018 Most "Soil space occupancy" traits can be important for this function.…”
Section: Plant P Acquisitionmentioning
confidence: 99%
“…Whole root system, absorptive roots Lambers et al, 2008;Ros et al, 2018 Most traits associated to "Plant P acquisition", including traits associated to "Soil space occupancy", can be important for this process. The capacity of plants to acquire P from soil, with or without mycorrhizal symbiosis, across a range of locations in the soil influences P cycling.…”
Section: Accepted Articlementioning
confidence: 99%